Level of motivation amongst health personnel working in a Tertiary care Government Hospital of New Delhi, India - Poonam Jaiswal; Ashok K Singhal; Adesh K Gadpayle; Sandeep Sachdeva; Rabindra Padaria (Wolters Kluwer Medknow Publications, 2014)
Aims: To assess the level and factors of motivation amongst permanent government employees working in a tertiary health care institution. Material and Methods: A sample of 200 health personnel (50 in each category) i.e. doctors, nurses, technician, and support staff were contacted through face to face interview. Motivation was measured as the degree to which an individual possessed various identified motivation domains like Drive, Control, Challenge, Relationship and Rewards. Each domain was represented by 4 dimensions- accordingly a closed-ended statement represented each of these dimensions and responses were assessed on a Likert based scale. Data management was done using SPSS, ver. 19. Results: The average age for different health personnel were: Doctors 48.68 (±8.53), nurses 40.72 (±7.76), technician 38.4 (±10.65) and support staff 43.24 (±9.52) years. The average year of work experience was: Doctor 19.09 (±9.77), nurses 17.2 (±8.420), technician 14.84 (±10.45), support staff 18.24 (±10.28). A comparison of overall motivation index (mean score) revealed that nurse had highest level (3.47), followed by support staff (3.46), doctor (3.45) and technician (3.43). Based on their individual mean scores, the healthcare providers were categorised into three different levels of motivation and it was found that majority of the health personnel i.e.70% of support staff, 62% nurse, 56% doctor and technician, had high to very high level of motivation index. The mean scores for all the five factors as well as their respective ranks were also found out and it was deduced that "relationship" assumed first rank for doctors (mean score: 3.71) and technician (mean score: 3.75), whereas "control" assumed greatest significance for nurses (mean score, 3.62) and support staff (mean scores, 3.61). Based upon the mean scores, "reward" assumed third rank among all the four categories. Kruskal-Wallis test was applied to test if the different categories of health personnel varied with respect to five factors of motivation and it was found that their orientation towards the various motivational components differed significantly only with respect to Drive (P < 0.01). Conclusion: There is scope for enhancing staff motivation.